Antagomirs Targeting MiroRNA-134 Attenuates Epilepsy in Rats through Regulation of Oxidative Stress, Mitochondrial Functions and Autophagy - Sun, Jiahang; Gao, Xiaoying; Meng, Dawei; Xu, Yang; Wang, Xichun; Gu, Xin; Guo, Mian; Shao, Xiaodong; Yan, Hongwen; Jiang, Chuanlu; Zheng, Yongri (Frontiers in Pharmacology, 2017)
The effects of the existing anti-epileptic drugs are unsatisfactory to almost one third of epileptic patients. MiR-134 antagomirs prevent pilocarpine-induced status epilepticus. In this study, a lithium chloride-pilocarpine-induced status epilepticus model was established and treated with intracerebroventricular injection of antagomirs targeting miR-134 (Ant-134). The Ant-134 treatment significantly improved the performance of rats in Morris water maze tests, inhibited mossy fiber sprouting in the dentate gyrus, and increased the survival neurons in the hippocampal CA1 region. Silencing of miR-134 remarkably decreased malonaldehyde and 4-hydroxynonenal levels and increased superoxide dismutase activity in the hippocampus. The Ant-134 treatment also significantly increased the production of ATP and the activities of mitochondrial respiratory enzyme complexes and significantly decreased the reactive oxygen species generation in the hippocampus compared with the status epilepticus rats. Finally, the Ant-134 treatment remarkably downregulated the hippocampal expressions of autophagy-associated proteins Atg5, beclin-1 and light chain 3B. In conclusion, Ant-134 attenuates epilepsy via inhibiting oxidative stress, improving mitochondrial functions and regulating autophagy in the hippocampus.